Development, feasibility, and acceptability of an intervention to improve care for agitation in people living in nursing homes with dementia nearing the end-of-life. (15th October 2021) - Sampson, Elizabeth L.; Barber, Julie; Gillam, Juliet; La Frenais, Francesca; Lambe, Katie; Laybourne, Anne; Manela, Monica; Marston, Louise; Moore, Kirsten; Panca, Monica; Stringer, Aisling; Webster, Lucy; et al.
ABSTRACT: Objectives: To develop a staff training intervention for agitation in people with severe dementia, reaching end-of-life, residing in nursing homes (NHs), test feasibility, acceptability, and whether a trial is warranted. Design: Feasibility study with pre- and post-intervention data collection, qualitative interviews, and focus groups. Setting: Three NHs in South East England with dementia units, diverse in terms of size, ownership status, and location. Participants: Residents with a dementia diagnosis or scoring ≥2 on the Noticeable Problems Checklist, rated as "severe" on Clinical Dementia Rating Scale, family carers, and staff (healthcare assistants and nurses). Intervention: Manualized training, delivered by nonclinical psychology graduates focusing on agitation in severe dementia, underpinned by a palliative care framework. Measurements: Main outcomes were feasibility of recruitment, data collection, follow-up, and intervention acceptability. We collected resident, family carer, and staff demographics. Staff provided data on resident's agitation, pain, quality of life, and service receipt. Staff reported their sense of competence in dementia care. Family carers reported on satisfaction with end-of-life care. In qualitative interviews, we explored staff and family carers' views on the intervention. Results: The target three NHs participated: 28 (49%) residents, 53 (74%) staff, and 11 (85%) family carers who were eligible to participate consented. Eight-four percent of staff attended ≥3 sessions, and we achieved 93% follow-up. We were able to complete quantitative interviews. Staff and family carers reported the intervention and delivery were acceptable and helpful. Conclusions: The intervention was feasible and acceptable indicating a larger trial for effectiveness may be warranted.